2018
DOI: 10.1177/0013916518794260
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Employees’ Work Patterns and Office Type Fit (and Misfit) in the Relationships Between Employee Well-Being and Performance

Abstract: Nearly half of workers agree that their workspace is unsuitable for their work tasks. Furthermore, it is assumed that happy workers often perform better than unhappy ones. Nevertheless, due to the effect of the emotional-cognitive processes, the misfit between employees’ office type and their work patterns (complexity and interactivity) may hamper this relationship between well-being and performance. This diary study on 83 office workers ( n = 603 time points) combines information about work patterns identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 86 publications
2
21
1
Order By: Relevance
“…We did not find any studies on the links between MoW and creative or counterproductive indicators of performance. Our review also found one study [50] that analyzed two relationships between activity worthwhileness, a similar construct to MoW, and employee performance. One of them showed a positive link between activity worthwhileness and contextual performance for workers whose physical office spaces (e.g., open-plan offices, individual offices) fit their job patterns (i.e., their task complexity and required interaction with others), whereas no significant relationships were found in workers with no fit.…”
Section: Ewb Future-oriented Conceptualizationsmentioning
confidence: 89%
See 1 more Smart Citation
“…We did not find any studies on the links between MoW and creative or counterproductive indicators of performance. Our review also found one study [50] that analyzed two relationships between activity worthwhileness, a similar construct to MoW, and employee performance. One of them showed a positive link between activity worthwhileness and contextual performance for workers whose physical office spaces (e.g., open-plan offices, individual offices) fit their job patterns (i.e., their task complexity and required interaction with others), whereas no significant relationships were found in workers with no fit.…”
Section: Ewb Future-oriented Conceptualizationsmentioning
confidence: 89%
“…In the organizational context, it has been defined as a holistic sensation characterized by absorption, work enjoyment, and intrinsic work motivation [46]. Although some authors describe the flow experience as a close variant of positive effect [47], a large number of recent studies describe flow as a momentary form of eudaimonic well-being [48][49][50][51], mainly because it has been shown that people can experience flow even without describing it as pleasant [32]. In the present systematic review, we found a total of seven relationships, six of them describing significant and positive links between flow and task (three relationships), contextual (one relationship), and creative (two relationships) performance, and one non-significant relationship with contextual performance, mostly providing support for the happy-productive worker thesis.…”
Section: Empirical Evidence On Ewb-performance Relationships In the Hpwtmentioning
confidence: 99%
“…However, Vischer [32] and Gerdenitsch et al [33] suggested that the type of office used for task implementation can have an influence on employee work outcomes. Additionally, empirical evidence by Soriano et al [34] confirmed that an adequate office type for the task can boost employees' well-being, which in turn impact on their in-role and extra-role performance. While psychological empowerment [35] and office design have been separately linked to OCB [34], to date, no study has illuminated how these two types of relationships interact to influence employee OCB.…”
Section: Introductionmentioning
confidence: 98%
“…Additionally, empirical evidence by Soriano et al [34] confirmed that an adequate office type for the task can boost employees' well-being, which in turn impact on their in-role and extra-role performance. While psychological empowerment [35] and office design have been separately linked to OCB [34], to date, no study has illuminated how these two types of relationships interact to influence employee OCB. In this study, we examine the moderation effect of office setting on the relation between psychological empowerment and OCB.…”
Section: Introductionmentioning
confidence: 98%
“…need-supply fit" (Gerdenitsch et al, 2018;Wohlers et al, 2019), "work pattern-office type (mis)fit" (Soriano et al, 2018), and one component of "person-environment fit" (a broader concept which also includes congruence with the broader psychosocial and organisational environment; Edwards and Billsberry, 2010). In line with the ED-R model, previous studies have confirmed a significant positive association between perceptions of alignment and productivity (Gerdenitsch et al, 2017;Soriano et al, 2018;Wohlers et al, 2019). Consequently, practitioners should perform more comprehensive evaluations of demands, resources, and crafting opportunities within the workplace environment, to get a truer understanding of workplace effectiveness.…”
Section: Insert Figure 1 Herementioning
confidence: 99%